Key Variables In Strengthening Rural-Urban Linkages In Pandeglang Regency - Devi Triady Bachruddin; Akhmad Fauzi; Bambang Juanda; Hania Rahma (Journal of Governance, 2026)
Rural-urban linkage is an essential element in sustainable regional development as it reflects the reciprocal relationship between rural and urban areas through the flow of people, goods, services, information, capital, and institutions. Pandeglang Regency, as one of the predominantly rural areas in Banten Province, still faces various challenges in the form of infrastructure inequality, limited access to basic services, low economic connectivity, and weak inter-regional integration. This study aims to analyze the key variables that influence the strengthening of rural-urban linkages in Pandeglang Regency using the MICMAC (Matrix of Cross Impact Multiplications Applied to Classification) approach. The analysis was conducted on 15 main variables representing the dimensions of infrastructure, economy, social, digital, institutional, and governance. The results show that the variables of Governance Quality (GOQ), Government Program Support (GPS), Inter Regional Cooperation (IRC), Village Road Quality (VRQ), and Internet Signal Quality (ISQ) are situated in the quadrant of high influence and low dependence, thus acting as the main driving variables. These findings indicate that the strengthening of rural-urban linkages in Pandeglang is highly influenced by institutional capacity, infrastructure connectivity, and cross-regional policy integration. This research provides novelty through the development of a rural-urban linkage model based on MICMAC analysis at the regency level using multidimensional indicators.